ANALISIS PENGARUH TATA KELOLA PERUSAHAAN DAN FINANCIAL LEVERAGE TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Panjaitan, Melyana Santy Apriani; Wage, Sunarto (LPPM Universitas Putera Batam, 2021)
This study explains the significant effect of corporate governance which is a proxy for managerial ownership and financial leverage either partially or simultaneously on the value of manufacturing companies in the consumer goods industry sector recorded on the IDX for the 2015-2019 period. Data were analyzed using multiple linear regression analysis techniques. Purposive sampling is used as the method of determining the sample in this study to obtain 10 sample companies from 61 companies with the criteria of companies listed on the IDX, which have published their financial reports consistently throughout the 2015-2019 period that have been audited and companies that have complete data on managerial ownership. , Debt to Equity Ratio and Price to Book Value in 2015-2019 in consumer goods industrial sector manufacturing companies listed on the IDX. The data source used in this study is secondary data. The test results of this study were carried out partially governance proxied by managerial ownership which has a significant effect on firm value and financial leverage has no significant effect on firm value. Simultaneously (simultaneously) corporate governance proxied by managerial ownership and financial leverage has a significant effect on firm value.